2015
DOI: 10.3897/zookeys.488.8919
|View full text |Cite
|
Sign up to set email alerts
|

Two new species of the genus Diostracus Loew from Tibet, with a key to the Himalayan fauna (Diptera, Dolichopodidae)

Abstract: Previously only one species of the genus Diostracus was known to occur in Tibet. Here the following two new species are added to the fauna of Tibet: Diostracus acutatus sp. n. and Diostracus tibetensis sp. n. Their relationships with similar species are discussed. A key to the species of Diostracus from the Himalayas is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Before our study, 101 species of the genus had been reported ( Zhu 2006 ; Zhu et al 2007a , b ; Grichanov 2013 , 2015 , 2017 ; Pusch 2014 ; Wang et al 2015 ). The first Diostracus , D. prasinus Loew, was named in 1861 from the Nearctic Region, whereas most species of the genus were reported from the Palaearctic and Oriental realms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Before our study, 101 species of the genus had been reported ( Zhu 2006 ; Zhu et al 2007a , b ; Grichanov 2013 , 2015 , 2017 ; Pusch 2014 ; Wang et al 2015 ). The first Diostracus , D. prasinus Loew, was named in 1861 from the Nearctic Region, whereas most species of the genus were reported from the Palaearctic and Oriental realms.…”
Section: Introductionmentioning
confidence: 99%
“…The first Diostracus , D. prasinus Loew, was named in 1861 from the Nearctic Region, whereas most species of the genus were reported from the Palaearctic and Oriental realms. Remarkably, Diostracus shows great diversity in the Himalayas, which is the junctions of the two realms, and 39 species have been reported from this area ( Zhu 2006 ; Wang et al 2015 ). Tibet is located in the east of the Himalaya Mountains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diostracus Loew, 1861, Sphyrotarsus Mik, 1874, Lagodechia Negrobov, Tsurikov, 1996, and Ozmena Özdikmen, 2010. Saigusa [1984, 1995 and Wang et al [2015] Description. Male (Fig.…”
Section: Genus Diostracus Loew 1861mentioning
confidence: 99%
“…It was recently reviewed by Yang et al [2011] for the Chinese fauna, Grichanov [2013] for the West Palaearctic fauna (including Pamirs), and Wang et al [2015] for the Himalayan fauna. Four species were described from the northernmost mountains of Myanmar [Saigusa, 1995].…”
mentioning
confidence: 99%